2016
DOI: 10.1111/jfpe.12390
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Airflow and Heat Transfer During Forced‐Air Precooling of Apples

Abstract: In this work, we study how different air-inflow velocities affect the appletemperature distribution during forced-convection cooling of individual apples by simultaneously modeling airflow and heat transfer. In general, an increase in airflow velocity increases the cooling rate and heat transfer fluxes across the apple surface and decreases cooling time. The results show that a reasonable increase in cooling rate is obtained with an increase in airflow velocity to 2.5 m/s; any further increase in airflow veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
4
26
2
Order By: Relevance
“…Among regression constants, the cooling coefficient ( k 2 ) is related to the rate at which a product is cooled and expresses the change of fruit temperature divided by cooling time and by difference of temperature between the product and the surrounding air (Brosnan & Sun, ). Data showed that there was a correlation between air velocity and k 2 , which confirmed that as air flowed faster the cooling time was smaller (Table ), which has also been reported for other cooling processes (Han et al, ). The position of fruit inside the system affected cooling parameters, and k 2 was higher at the input and smaller at the output, which coincided with the smaller value of t 7/8 at the input than that of the output.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Among regression constants, the cooling coefficient ( k 2 ) is related to the rate at which a product is cooled and expresses the change of fruit temperature divided by cooling time and by difference of temperature between the product and the surrounding air (Brosnan & Sun, ). Data showed that there was a correlation between air velocity and k 2 , which confirmed that as air flowed faster the cooling time was smaller (Table ), which has also been reported for other cooling processes (Han et al, ). The position of fruit inside the system affected cooling parameters, and k 2 was higher at the input and smaller at the output, which coincided with the smaller value of t 7/8 at the input than that of the output.…”
Section: Resultssupporting
confidence: 82%
“…The coefficient h varied between 3.7 and 100.6 W/m 2 °C and was affected by air velocity ( v air ) during cooling, in a way that as v air was higher the coefficient h increased significantly (Table ). This was also an expected result, since it is well documented that a thermal convection coefficient is highly dependent on medium velocity (Han et al, ). On the other hand, the input of the system operated with the highest value of h , followed by the intermediate zone, and finally by the output one, with significant difference between all of them (Table ).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, it is of great interest to perform an analysis of the process of turbulent flow and air distribution in a fully three-dimensional way, which implies a load not negligible on both computational and in the features and scope of the model [5]. A complete model of the drying process must take into consideration the interaction between heat-and-mass transfer within the material to be dried and the transfer to the drying air flow [9], several studies have been carried out in these aspects and their combinations, both at the simulation of models and at experimental levels performed by Cârlescu et al [10], Villegas et al [11], Lemus-Mondaca et al [5] ( [12]), Han et al [13], Gómez & Ochoa [14], Ozgen [15], Mohan [6], Lamnatou [9] among many others.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the reliability of aerodynamic simulation results is reduced and the effect of evaporative cooling is not modeled explicitly. Han et al (2017) found that the maximum temperature difference of a single apple was up to 0.033°C during cooling by comparing the temperature simulated with or without considering respiratory heat. Regarding strawberries, Nalbandi and Seiiedlou (2020) reported that transpiration heat could not be neglected during the cooling process, as the 7/8ths cooling time (SECT) decreased by 31% when this heat was added into the numerical model.…”
mentioning
confidence: 99%